PUBLIC ENVIRONMENTAL EDUCATION IN THE FIELD OF ECO-LABELLING - SOBCZYK, Wiktoria; WOJCIK, Agnieszka Katarzyna (Trends in education, 2013)
The idea of introducing of ecological labels (eco-labelling) on products, which are less harmful to the environment, emerged in the XXth century. Ecoproduct is a product that production, utilization and recycling is in terms of environmental and social requirements improved as compared to a conventional product. Eco-labeling enables the consumers to clearly identify ``green'' products. Surveys have shown, that ecological labeling of goods is recognized in a very limited scale. Therefore, there is a need for a broad ecological information campaign for consumers.
Keywords: eco-labeling; environmental education; ecological product